2019
DOI: 10.22373/ej.v6i1.2514
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Use of L1 in L2 Classroom

Abstract: Using mother tongue (L1) in a foreign language (L2) classrooms is inevitable. Despite the debate over the adequacy of using L1 in the teaching of L2, this paper argues using L1 in the classroom does not hinder learning, and that L1 has a facilitating role to play in the classroom and can help L2 learning and acquisition. This paper shows that L1 is an inseparable part of language teaching, and it has several functions for both the students and teachers in English language learning and teaching. Therefore, thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 7 publications
0
19
0
1
Order By: Relevance
“…As to the specific functions of using L1 as metatalk, H-H pair used it only for the clarification of lexical items while H-L pair used it for a wider range from grammar explanations to lexical items and private speech. It is clear that L1 use acted in line with the proficiency levels of the pairs, namely by assisting H-L pair more frequently and functionally than it did H-H. One thing is certain that L1 use helped both pairs initiate and continue their collaborative dialogue (as stated by Zulfikar, 2018), and in different amounts and for different functions, it promoted collective inquiry. This fact is obvious from the exchanges above in which both pairs made use of L1 to regulate their thoughts, clarify the puzzles and create learning experiences in general.…”
Section: Excerpt 15mentioning
confidence: 90%
See 2 more Smart Citations
“…As to the specific functions of using L1 as metatalk, H-H pair used it only for the clarification of lexical items while H-L pair used it for a wider range from grammar explanations to lexical items and private speech. It is clear that L1 use acted in line with the proficiency levels of the pairs, namely by assisting H-L pair more frequently and functionally than it did H-H. One thing is certain that L1 use helped both pairs initiate and continue their collaborative dialogue (as stated by Zulfikar, 2018), and in different amounts and for different functions, it promoted collective inquiry. This fact is obvious from the exchanges above in which both pairs made use of L1 to regulate their thoughts, clarify the puzzles and create learning experiences in general.…”
Section: Excerpt 15mentioning
confidence: 90%
“…Other lines of research have been exclusively dedicated to the use of L1 in collaborative dialogue (Colina & Mayo, 2009;Rayati et al, 2012;Storch & Wigglesworth, 2003;Zulfikar, 2018). As one of the influential studies in this domain, Storch & Wigglesworth (2003) identified the major areas where learners used L1 in writing tasks:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many English Language Teaching researchers advocate that L1 can play a facilitating role in the teaching of English L2 (Carson & Kashihara, 2012;Grim, 2010;Lightbown & Spada, 2020;Zulfikar, 2019), implying that teachers who speak learners' L1 are at an advantage especially when dealing with learners who all speak the same L1. However, excessive L1 use can be counterproductive in second or foreign language learning as it may hamper learners' acquisition of the target language.…”
Section: Lesson Planning and Developmentmentioning
confidence: 99%
“…• El uso estratégico de la L1 en el aula de idiomas puede estar justificado en ciertos momentos, tal y como establece el "Balanced Approach" (Nation, 2003). Con todo, existe también el riesgo de que si los docentes conocen o comparten la L1 de su alumnado, pueden hacer un uso desmedido (Miles, 2014). Esto último puede implicar que el uso de la L1 no se limite a momentos de auténtica necesidad (por ejemplo: situaciones de estrés severo), sino que llegue a sistematizarse ante cualquier contratiempo lógico derivado del desarrollo en LE de los aprendientes y, con ello, implique su aceptación por parte de todos los agentes implicados en el proceso de enseñanza-aprendizaje.…”
Section: Respuestas Preguntaunclassified